2009
DOI: 10.1111/j.1525-1594.2008.00696.x
|View full text |Cite
|
Sign up to set email alerts
|

Possible Role of Artificial Oxygen Carriers in Transfusion Medicine: A Retrospective Analysis on the Current Transfusion Practice

Abstract: Artificial oxygen carriers (AOC) are under development as a substitute for red blood cells (RBC) in homologous transfusion (Tx). The lack of surface antigen in AOC makes ABO-typing and antibody-screening (T/S) unnecessary. Pathogen elimination renders it much safer, and long-term stability allows ubiquitous storage for emergency use. To delineate the utility of AOC, we retrospectively examined current Tx practices in Tokai University and the Japanese Red Cross Society. The emergency department of Tokai Univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…Clinical needs for transfusion often derive from trauma and/or surgery, involving concurrent exposure to pathogens and/or tumor antigens. We have been using type O Rh (+)‐washed and ‐packed RBCs for emergency transfusion for patients with hemorrhagic shock before identical RBCs become available (12). Although a shortened ischemic period has been demonstrated to be advantageous in terms of survival over the risk of minor mismatch transfusion (12), the volume of transfusion derived from a 400‐mL package amounted to 3.05 ± 1.20 units of washed and packed RBCs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical needs for transfusion often derive from trauma and/or surgery, involving concurrent exposure to pathogens and/or tumor antigens. We have been using type O Rh (+)‐washed and ‐packed RBCs for emergency transfusion for patients with hemorrhagic shock before identical RBCs become available (12). Although a shortened ischemic period has been demonstrated to be advantageous in terms of survival over the risk of minor mismatch transfusion (12), the volume of transfusion derived from a 400‐mL package amounted to 3.05 ± 1.20 units of washed and packed RBCs.…”
Section: Discussionmentioning
confidence: 99%
“…Circulation half‐life (T 1/2 ) of LEH and HbV depends on species as well as doses; it is approximately 1 day in rodents (4–9) and 2–3 days in primates when 10–20 mL/kg is used (10,11). While LEH is removed from the circulation and disposed of by the reticuloendothelial system (RES) similarly to RBCs, the possible use of LEH for emergency transfusion before identical donor blood becomes available (12) may impose an acute metabolic load of hemoglobin and lipids on RES or antigen‐presenting cells (APCs), such as dendritic cells (DCs) or macrophages, which plays a pivotal role in the triggering of the host's immune defense against third‐party antigens. Thus, this raises a serious concern, as hemorrhagic shock patients are often exposed to pathogens at accidents or surgery causing acute blood loss necessitating emergency transfusion (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although liposomes are much smaller (230 nm), their O 2 -carrying capacity is equivalent to human RBCs under room air respiration (Kaneda et al, 2009). These physical characteristics prompted us to examine the therapeutic potential of LEH, not as an RBC substitute (Yoshiba et al, 2009), in a rodent model of photochemically induced thrombosis of the middle cerebral artery (MCA) (Kawaguchi et al, 2007) and showed that the cortex was significantly better protected than basal ganglia in 24 h. Here, the effects of LEH were quantitatively assessed by steady-state 15 O-gas inhalation…”
Section: Introductionmentioning
confidence: 99%
“…Although liposomes are much smaller (230 nm), their O 2 -carrying capacity is equivalent to human RBCs under room air respiration (Kaneda et al, 2009). These physical characteristics prompted us to examine the therapeutic potential of LEH, not as an RBC substitute (Yoshiba et al, 2009), in a rodent model of photochemically induced thrombosis of the middle cerebral artery (MCA) (Kawaguchi et al, 2007) and showed that the cortex was significantly better protected than basal ganglia in 24 h. Here, the effects of LEH were quantitatively assessed by steady-state 15 O-gas inhalationThis work was supported in part by a grant-in-aid for scientific research from The Ministry of Education, Culture, Science, and Technology, Tokyo, Japan [Grants 14370365, 16209037, 20249072]; New Energy Development Organization, Tokyo, Japan; Japan Science and Technology Agency, Tokyo, Japan; and CREST, Japan Science and Technology Agency, Saitama, Japan.Article, publication date, and citation information can be found at http://jpet.aspetjournals.org. doi:10.1124/jpet.109.160051.…”
mentioning
confidence: 99%